2018
DOI: 10.1186/s12889-018-5845-3
|View full text |Cite
|
Sign up to set email alerts
|

Higher vegetable intake and vegetable variety is associated with a better self-reported health-related quality of life (HR-QoL) in a cross-sectional survey of rural northern Ghanaian women in fertile age

Abstract: BackgroundA higher vegetable intake plays an important role in promoting general health and well-being, but there is a dearth of data on the independent effect of vegetable intake on health-related quality of life (HR-QoL). This study contributes to evidence on the independent effect of vegetable consumption on HR-QoL among women in fertile age.MethodsA cross-sectional study of a sample of rural women in fertile age (15–49 years, n = 187), randomly selected from 6 rural communities in the Tolon and Savelugu Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
4
15
1
1
Order By: Relevance
“…The systematic review of the observational studies analyzing the association between the intake of fruit and vegetable and mental health in adults revealed the possible beneficial influence of the indicated products. This association was studied for various aspects of mental health, ranging from general and mental well-being [35,45,49,62,68,77,82,84,94], quality of life [36,39,42,43,47,55,70], sleep quality [55], life satisfaction [50,66,82], flourishing [50], mood [50,62,68,77,81], self-efficacy [56], curiosity [68], creativity [68], optimism [91,93], self-esteem [90], stress [40,48,67,71,73,80,89,92], nervousness [82], or happiness [52,59,65,82], to anxiety [35,…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review of the observational studies analyzing the association between the intake of fruit and vegetable and mental health in adults revealed the possible beneficial influence of the indicated products. This association was studied for various aspects of mental health, ranging from general and mental well-being [35,45,49,62,68,77,82,84,94], quality of life [36,39,42,43,47,55,70], sleep quality [55], life satisfaction [50,66,82], flourishing [50], mood [50,62,68,77,81], self-efficacy [56], curiosity [68], creativity [68], optimism [91,93], self-esteem [90], stress [40,48,67,71,73,80,89,92], nervousness [82], or happiness [52,59,65,82], to anxiety [35,…”
Section: Discussionmentioning
confidence: 99%
“…Three studies included child participants [18,33,34] and four studies included adolescent participants [35][36][37][38]. Thirty-seven studies included adult participants [14][15][16][17]19,[21][22][23][24][25][26]31,32,; seven studies included a combination of children or adolescents and adults [63][64][65][66][67][68][69].…”
Section: Study Design and Samplesmentioning
confidence: 99%
“…The cross-sectional study design was the most common design among the included studies (Table 3), reported in 23 papers [15,18,[34][35][36][38][39][40][41][42][43][44][45]47,[51][52][53]58,[63][64][65]67,68]. These studies included analysis of existing, ongoing national surveillance datasets in the United States [15,18,44], cross-sectional studies in USA [47,51], and in international populations [34][35][36][38][39][40][41][42][43]45,52,63,65,67]. Cross-sectional analyses from prospective cohort studies were also included [40,43].…”
Section: Study Design and Samplesmentioning
confidence: 99%
See 2 more Smart Citations